2009
DOI: 10.1128/iai.00764-08
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bacillus anthracis Capsule with Lethal Toxin during Experimental Infection

Abstract: Bacillus anthracis lethal toxin (LT) was characterized in plasma from infected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 35 publications
1
36
1
Order By: Relevance
“…γDPGA not only is found on the surface of vegetative bacteria but also has also been reported to occur in a soluble form during the systemic phase of the infection (19). Some of the soluble γDPGA was found to be associated with lethal toxin, raising the possibility that γDPGA may play a novel and unexpected role in anthrax pathogenesis (25). Therefore, anti-γDPGA mAbs may have protective effects that extend beyond their demonstrated ability to promote opsonophagocytic killing of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…γDPGA not only is found on the surface of vegetative bacteria but also has also been reported to occur in a soluble form during the systemic phase of the infection (19). Some of the soluble γDPGA was found to be associated with lethal toxin, raising the possibility that γDPGA may play a novel and unexpected role in anthrax pathogenesis (25). Therefore, anti-γDPGA mAbs may have protective effects that extend beyond their demonstrated ability to promote opsonophagocytic killing of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The γ-DPGA capsule produced by B. anthracis constitutes the other key virulence factor of anthrax disease. A recent report revealed that γ-DPGA and lethal toxin may interact (27). Also, 10-50-kDa fragments of γ-DPGA were reported to enhance LT-mediated killing of J774A.1 cells (29).…”
Section: D2-d4 Interface Senses Capsule and Protons During Channelmentioning
confidence: 99%
“…Whereas the PA monomer, LF, and EF can bind to capsule, the PA prechannel oligomer binds most avidly to the capsule in the nanomolar range. In vivo, only preassembled LT, LF, and proteolytically active PA 63 (and not full-length PA 83 ) are observed in the plasma (27); however, for these fractions of the toxin to function, they must be assembled, stabilized, and capable of sensing their environment. The stabilization of PA prechannels by γ-DPGA may maintain their thermostability in vivo, because premature channel formation inactivates the toxin (10).…”
Section: D2-d4 Interface Senses Capsule and Protons During Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, industrial production of c-PGA from B. anthracis is not viable owing to its toxicity. In fact, the anchored c-PGA is responsible for the non-immunogenic capsule of B. anthracis, which has been associated with the lethal toxin (Ezzell et al, 2009). Hence, to render B. anthracis immunogenic, its cap gene responsible for the anchoring of c-PGA onto its surface needs to be targeted (Candela & Fouet, 2006).…”
Section: Other Bacteriamentioning
confidence: 99%